1996
DOI: 10.1074/jbc.271.16.9281
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Human Recombinant Granzyme A Zymogen and Its Activation by the Cysteine Proteinase Cathepsin C

Abstract: Human granzyme A is one of the serine proteinases present in the granules of cytotoxic T lymphocytes and natural killer cells. Granzymes are synthesized as inactive proenzymes with an amino-terminal prodipeptide, which is processed during transport of granzymes to the cytotoxic granules, where they are stored as active proteinases. In this study, we explored the possibility of producing recombinant granzymes. Recombinant human granzyme A zymogen was expressed in several eukaryotic cell lines (HepG2, Jurkat, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 35 publications
1
49
0
Order By: Relevance
“…We first used GF.dmk, a synthetic peptide that readily enters the cells and that specifically and irreversibly inhibits the activity of DPPI, a lysosomal thiol protease with dipeptidyl aminopeptidase activity that is required for post-transational processing and activation of many myeloid and lymphoid granule-associated serine proteases (13,(23)(24)(25)(26). Enriched in cytolytic granules of CTL (27) and coordinately expressed with GrA during CD8 ϩ T cell development and differentiation (28), DPPI is the sole protease that performs in vivo the proteolytic activation of the proenzyme forms of GrA and GrB (29).…”
Section: Partial Processing Of Procaspase-3 Is Preferentially Initiatmentioning
confidence: 99%
See 1 more Smart Citation
“…We first used GF.dmk, a synthetic peptide that readily enters the cells and that specifically and irreversibly inhibits the activity of DPPI, a lysosomal thiol protease with dipeptidyl aminopeptidase activity that is required for post-transational processing and activation of many myeloid and lymphoid granule-associated serine proteases (13,(23)(24)(25)(26). Enriched in cytolytic granules of CTL (27) and coordinately expressed with GrA during CD8 ϩ T cell development and differentiation (28), DPPI is the sole protease that performs in vivo the proteolytic activation of the proenzyme forms of GrA and GrB (29).…”
Section: Partial Processing Of Procaspase-3 Is Preferentially Initiatmentioning
confidence: 99%
“…DPPI is a thiol protease with aminodipeptidase activity required for the activation of many granule-associated serine proteases. In T lymphocytes, it is predominantly located in the cytolytic granules of CTL (27,28), where it performs the proteolytic maturation/activation of proGrA and proGrB (13,23,24,29). We therefore assumed that a granule-associated serine protease dependent on DPPI activity was in charge of procaspase-3 processing.…”
Section: ) In Cd4mentioning
confidence: 99%
“…Evidence that amount of prochymase secreted into the culture supernatant by High Five cells was 6.3-times and 13-times greater than that DPP I might be the enzyme responsible for the processing of granulocyte proteases in vivo comes from its ability to catalyse produced by Sf9 and Sf21 cells, respectively. For production of recombinant prochymase, 500 ml cells at a density of 1.8Ϫ this reaction in vitro [20,21,25], its greater abundance in cells which secrete them [22,26], and the inhibition of granulocyte 2.2ϫ10 6 ml Ϫ1 were inoculated with the transformed baculovirus at a multiplicity of infection of 5, and the supernatant harvested protease activation by the addition of the specific DPP I inhibitor Gly-Phe-diazomethyl ketone to cells in culture [18,26,27].…”
mentioning
confidence: 99%
“…In addition, DPPI activity was found to colocalize with serine protease activity (such as granzyme A tryptase activity) in the specialized granule fraction of CTL (14). Several studies have also demonstrated the ability of DPPI to directly cleave the prodipeptide of various serine proteases, thereby activating them (16,17). To examine whether the expression of DPPI is regulated during in vitro lymphocyte activation, we examined DPPI mRNA and protein levels, and DPPI activity (using a defined synthetic substrate) in resting splenocytes, or splenocytes activated with various protocols (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have also suggested that DPPI activity, although present in a wide variety of tissues, is significantly higher in cytotoxic lymphocytes and myeloid cells (13)(14)(15); in these cells, DPPI localizes to the secretory granule compartment and may be the major enzyme responsible for processing serine proteases from the proenzyme form to the catalytically active form (14,15). Finally, two different reports have shown that DPPI can directly cleave the activation prodipeptides of granzymes A and B (16,17), serine proteases that are found in the secretory granules of activated cytotoxic lymphocytes (CTL) and natural killer cells (18).…”
mentioning
confidence: 99%